EVALUASI KINERJA SISTEM RANTAI PASOKAN MEJA TENIS MEJA MENGGUNAKAN METODE SUPPLY CHAIN OPERATION REFERENCE - Fitri Nurul Firdaus; Yuniaristanto Y; Roni Zakaria (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
This study aims to map the process and to measure the performance of supply chain of table tennis at CV Shiamiq Terang Abadi according to SCOR®11.0 model. Furthermore, this study would give suggestion of improvement in order to improve company's performance. The SCOR®11.0 model is considered more complete, systematic and integrated because of its capability in measuring the company's performance from supplier to customer. Data collection in this study was conducted by questionnaire method to CV Shiamiq Terang Abadi which is related directly to the supply chain process. Based on SCOR®11.0 assessment, there are five KPIs that have not reached the company’s target and can be improved: POF, OFCT, USCA, TC and CCCT which has successive gap by 4%, 33 days, 24.05%, 7,38% and 9 days. There are sub-operations within the supply chain become inefficient metrics and need process improvement. The best practices of recomendations are four of the most prioritized: convergence of SCOR model with lean and six sigma, make-tostock goods receipt, ABC inventory classification, and batch size reduction